Интеграл Дюамеля и операционно-структурный метод в математическом моделировании нестационарных температурных процессов для областей неканонической формы - Бутенко, Т.В.; Слесаренко, А.П. (Вісник Харківського національного університету імені В.Н.Каразіна, 2009)
An analytical method is suggested of solution of the unsteady-state heat conduction problems for the complex-configuration regions with unsteady-state boundary conditions and energy sources. The method is based on the simultaneous use of the Duhamel integrals and operational-structural method. The calculation results are presented for one variant.
Keywords: задача теплопроводности; область сложной формы; нестационарные граничные условия; интеграл Дюамеля; метод Бубнова-Галеркина